Human Umbilical Mesenchymal Stem Cells-Derived Microvesicles Attenuate Formation of Hypertrophic Scar through Multiple Mechanisms - Qun Qian; Ni Zhu; Wenzhe Li; Songlin Wan; Dongcheng Wu; Yunhua Wu; Weicheng Liu (Stem Cells International)
Mesenchymal stem cells and the derived extracellular microvesicles are potential promising therapy for many disease conditions, including wound healing. Since current therapeutic approaches do not satisfactorily attenuate or ameliorate formation of hypertrophic scars, it is necessary to develop novel drugs to achieve better outcomes. In this study, we investigated the effects and the underlying mechanisms of human umbilical mesenchymal stem cells (HUMSCs)-derived microvesicles (HUMSCs-MVs) on hypertrophic scar formation using a rabbit ear model and a human foreskin fibroblasts (HFF) culture model. The results showed that HUMSCs-MVs reduced formation of hypertrophic scar tissues in the rabbit model based on appearance observation, and hematoxylin and eosin (H&E), Masson, and immunohistochemical stainings. HUMSCs-MVs inhibited invasion of HFF cells and decreased the levels of the α-SMA, N-WASP, and cortacin proteins. HUMSCs-MVs also inhibited cell proliferation of HFF cells. The MMP-1, MMP-3, and TIMP-3 mRNA levels were significantly increased, and the TIMP-4 mRNA level and the NF-kB p65/β-catenin protein levels were significantly decreased in HFF cells after HUMSCs-MVs treatment. The p-SMAD2/3 levels and the ratios of p-SMAD2/3/SMAD2/3 were significantly decreased in both the wound healing tissues and HFF cells after HUMSCs-MVs treatment. CD34 levels were significantly decreased in both wound healing scar tissues and HFF cells after HUMSCs-MVs treatment. The VEGF-A level was also significantly decreased in HFF cells after HUMSCs-MVs treatment. The magnitudes of changes in these markers by HUMSCs-MVs were mostly higher than those by dexamethasone. These results suggested that HUMSCs-MVs attenuated formation of hypertrophic scar during wound healing through inhibiting proliferation and invasion of fibrotic cells, inflammation and oxidative stress, Smad2/3 activation, and angiogenesis. HUMSCs-MVs is a potential promising drug to attenuate formation of hypertrophic scar during wound healing.